Is the E133K allele of VG5Q associated with Klippel-Trenaunay and other overgrowth syndromes?. Issue 7 (27th January 2006) - Barker, K T; Foulkes, W D; Schwartz, C E; Labadie, C; Monsell, F; Houlston, R S; Harper, J
Abstract : Background: It has been reported that the activating mutation, E133K, in the angiogenic factor VG5Q (formally named AGGF1) causes Klippel-Trenaunay Syndrome (KTS), a rare vascular disease associated with asymmetric overgrowth. This proposal followed from the observation that five out of 130 KTS patients were constitutionally heterozygous for VG5Q, E133K. Objective: To explore the possibility that VG5Q, and specifically E133K, is implicated in other mosaic overgrowth syndromes. Results: 24 patients were analysed for this sequence change. One patient was constitutionally heterozygous for E133K. Analysis of both parents revealed that the patient's mother, who was healthy, also carried E133K. An analysis of 275 healthy controls showed that 3.3% (9/275) of the population were carriers of E133K. Conclusions: The findings bring into question the assertion that VG5Q, E133K is a mutation and that it causes KTS.